Biografie di vasi. Il Vaso di Archemoros nella documentazione dell’Archivio Storico e della Fototeca dell’Instituto Archeologico Germanico - Giacobello, Federica (Römische Mitteilungen, 2024)
Since its foundation in 1829, the Institute of Archaeological Correspondence has played a fundamental role in scientific research, publishing news and studies of archaeological finds in its journals. To this end, the Institute relied on members and correspondents - antiquities scholars, collectors, excavators and art dealers - who provided prompt news and descriptions of finds from all over the Italian peninsula. The DAI Rome Historical Archive preserves valuable documentation of the letters sent by correspondents and the drawings produced to document the artefacts, as well as the plates published in Monumenti Inediti, that show a particular interest for the figured pottery. This documentation has made an important contribution in tracing the modern biography of the 'Vaso di Archemoros', apulian crater discovered in Ruvo di Puglia in 1834, that became part of the collection of the Real Museo Borbonico di Napoli.